Evaluation of apical debris extrusion during endodontic retreatment by different systems - Dadalti, Manoela Teixeira de Sant'Anna; Almeida, Natália Elissa Monçôres de; Ormiga, Fabíola; Risso, Patrícia de Andrade (European Journal of General Dentistry, 2020)
Aim: This study sought to evaluate the amount of apical debris extrusion during the removal of filling material (RFM) performed by the ProTaper-Retreatment (ProTaper-R), Mtwo-Retreatment (Mtwo-R), Reciproc, and hand files. Materials and Methods: Sixty lower premolars were prepared using the ProTaper Universal system and filled with thermoplastic technique. Subsequently, the samples were randomly divided into four groups (n = 15) according to the system used for the removal of the filling material: Mtwo-R (R25/.05); ProTaper-R (D1, D2, and D3); Reciproc (R25); and hand file (type K and Hedstroem stainless steel files). The apical debris extrusion was evaluated before and after the RFM from the root canal by weighing Eppendorf tubes on a high-precision balance. Statistical analysis was performed using the ANOVA test followed by the Tukey's test (P < 0.05). Results: All of the systems produced apical debris extrusion; however, the Mtwo-R group demonstrated significantly more extrusion as compared with the ProTaper-R and Reciproc groups (P < 0.05). There was no statistically significant difference between the Reciproc, ProTaper-R, and hand file groups (P > 0.05). Conclusions: The Mtwo-R group produced significantly more extrusion than did the ProTaper-R and Reciproc groups. There was no difference between the Reciproc, ProTaper-R, and hand file groups.
Keywords: Endodontic; filling materials; retreatment; root canal